(untitled) (Faridpur Medical College Journal, 2021)
Breast cancer is one of the common cancers in women that causes financial health burden and or death in Bangladesh. Economically we are slowly rising from low to middle income country, which is changing our women’s lifestyle. Risk factors of breast cancer include lifestyle factors like- age at first childbirth, parity, using oral contraceptives, BMI; which are also changing in our women. This study will look at our current incidence and patient profile of breast cancer patient. This is a retrospective study done in BIRDEM General Hospital. One hundred patient presenting with breast lump during the period of September 2018 -May 2019 were selected by purposive sampling. In <30 years age group 2 (13.6%) patient had cancer, 41% at <40 years, 53% in 51-60 , 83% in 61-70 age group. Thirty four out of 100 breast lump patient were diagnosed with cancer. Eleven had early cancer, 20 had locally advanced cancer, 3 presented with metastasis. In our study risk factor assessment did not show significant increase risk of in patients who are having cancer compared to those having benign breast disease with similar risk factors. The big number of advance and metastatic breast cancers in our study indicates self-breast examination and breast cancer screening program is still inadequate. Further research is required to find out breast cancer biology and pathogenesis rather than blindly accusing urbanized life style. Faridpur Med. Coll. J. 2020;15(2): 65-68